ANALYSIS SWOT CIVIC EDUCATION CURRICULUM FOR SENIOR HIGH SCHOOL YEAR 1975-2013 - Aim Abdulkarim, Gunawan Santoso, Suwarma Al Muchtar, (Jurnal Civicus, 2015)
Civics curriculum from year 1975-2013 are ultimately aims to make citizens say, act, and behave, based on Pancasila or spirit in everyday life that are run from the time school education to become a high school mature and become the pride of the nation bless yourself, family, school, state and nation with the moral soul/good and intelligent character who can advance and competitive in national and international era. Civics strength is on the Pancasila, the 1945 Constitution, values, morals, local knowledge and diversity in cultured. There are weaknesses in the teaching of Civics monotonous and more innovative not only focuses on the cognitive, affective and psychomotor while dispensed and not included on the national exam. Opportunities Civics still need a lot of development in the scientific body of knowledge. Threats of civics is free sex of number of students who make the nation weak morals and act not see the value of Pancasila (say and behave without values). Civics solution through a process of learning and practice of students in the school are monitored and assessed as a form of moral evaluation and student behavior.Â